Linezolid for the Treatment of Urinary Tract Infections Caused by Vancomycin-Resistant Enterococci - Mary Joyce Wingler; Neel R. Patel; S. Travis King; Jamie L. Wagner; Katie E. Barber; Kayla R. Stover (Pharmacy, 2021)
Vancomycin-resistant enterococci (VRE) account for a large proportion of hospital-acquired infections. Determining optimal treatment of VRE urinary tract infections (UTIs) is challenging. The purpose of this study was to determine if a difference in efficacy or safety exists between linezolid and non-linezolid treatments for VRE UTIs. This retrospective cohort evaluated patients admitted between 1 June 2012–30 November 2017 who were treated for VRE UTI. Patients must have had at least one sign, symptom, or laboratory confirmation of UTI to be included. The primary endpoint of this study was difference in clinical cure between linezolid and non-linezolid treatment options. Secondary endpoints included 30-day recurrence, 30-day infection-related readmission, inpatient mortality, infection-related hospital length of stay (LOS), and time to appropriate therapy. A total of 45 patients (33 linezolid and 12 non-linezolid) were included. Clinical cure occurred in 71.4% linezolid and 58.3% non-linezolid (p = 0.476). No patients had a 30-day infection-related readmission or 30-day recurrence. Of the 45 patients, 6 (13.3%) patients died during admission, and 5 of those deaths were in the linezolid group (p = 1.000). No significant difference was found for clinical cure between linezolid and non-linezolid treatment options for VRE UTIs.